2021
DOI: 10.3390/met11030431
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure-Based Modeling of the Effect of Inclusion on the Bendability of Advanced High Strength Dual-Phase Steels

Abstract: Advanced high strength dual-phase steels are one of the most widely sought-after structural materials for automotive applications. These high strength steels, however, are prone to fracture under bending-dominated manufacturing processes. Experimental observations suggest that the bendability of these steels is sensitive to the presence of subsurface non-metallic inclusions and the inclusions exhibit a rather discrete size effect on the bendability of these steels. Following this, we have carried out a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In summary, we have shown that even though the uniaxial stress-strain response of the low-carbon martensitic steel is not very sensitive to the variations in the heat-treatment parameters, their fracture response differs significantly. This is similar to dual-phase steels, for which it has been shown that the interaction of the heterogeneous deformation fields induced by the geometry of deformation, i.e., the presence of a notch in the single-edge notch specimens or three-point bending, and the material microstructure, i.e., distribution of a hard (martensite) and soft (ferrite) phases leads to an increase in the propensity of deformation localization, which significantly affects the fracture response of these materials [39][40][41]. The complex interactions of heterogeneous material microstructures and imposed loading conditions, and their effects on the observed mechanical response of materials, have also been observed under a host of other circumstances [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we have shown that even though the uniaxial stress-strain response of the low-carbon martensitic steel is not very sensitive to the variations in the heat-treatment parameters, their fracture response differs significantly. This is similar to dual-phase steels, for which it has been shown that the interaction of the heterogeneous deformation fields induced by the geometry of deformation, i.e., the presence of a notch in the single-edge notch specimens or three-point bending, and the material microstructure, i.e., distribution of a hard (martensite) and soft (ferrite) phases leads to an increase in the propensity of deformation localization, which significantly affects the fracture response of these materials [39][40][41]. The complex interactions of heterogeneous material microstructures and imposed loading conditions, and their effects on the observed mechanical response of materials, have also been observed under a host of other circumstances [42][43][44].…”
Section: Discussionmentioning
confidence: 99%